Globalism, Localism and Neo-Zapatism - Assies, Willem (European Review of Latin American and Caribbean Studies, 2003)
– La otra frontera; identidades múltiples en el Chiapas poscolonial, by Rosalva Aída Hernández Castillo. México: CIESAS, Miguel Ángel Porrúa, 2001. English edition: Histories and Stories from Chiapas; Border Identities in Southern Mexico. Austin: University of Texas Press. – Mayan Visions; The Quest for Autonomy in an Age of Globalization, by June C. Nash. New York and London: Routledge, 2001. – ¡Zapata Lives!; Histories and Cultural Politics in Southern Mexico, by Lynn Stephen. Berkeley, Los Angeles, London: University of California Press, 2002.